A nanodevice with lifetime-improved singlet oxygen for enhanced photodynamic therapy. Issue 42 (5th May 2022) - Cao, A-Min; Liu, Wen-Long; Zou, Mei-Zhen; Qin, Si-Yong; Cheng, Yin-Jia; Zhang, Ai-Qing
Abstract : A nanodevice was designed with functions of singlet oxygen production, storage and release to improve the lifetime of singlet oxygen for enhancing photodynamic therapy. Abstract : The short lifetime of singlet oxygen reduces its accumulation in the endoplasmic reticulum, which limits the output of photodynamic therapy. A nanodevice with functions of singlet oxygen production, storage and release can improve the lifetime of singlet oxygen for enhancing phototherapeutic efficacy.